Application of Calcium Aluminate-Based Materials for Direct Pulp Capping – In Vivo Study - Janković Ognjenka; Paraš Smiljana; Adamović Tijana; Latinović Ljiljana Tadić; Arbutina Radmila; Đukić Igor; Marin Saša; Bulajić Marko; Vukoje Karolina; Jokanović Vukoman; Pavlić Verica (Acta Veterinaria, 2025)
The aim of this paper is the histopathological assessment of the effects of a newly synthesized nanomaterial based on calcium aluminate ALBO-CA on the pulp of rat teeth. In 18 Wistar rats, 54 Class I cavities and exposed pulp of maxillary molars were treated with the tested materials: two experimental materials ALBO-CA (18 teeth), ALBO-CS (18 teeth), and MTA control (18 teeth), and cavities were restored with glass ionomer. The histopathological analysis included the following parameters: presence of pulp inflammation, degree of dentin bridge formation, and presence of bacteria in the pulp. Complete absence of pulp inflammation was noted in 12 (66.67 %) teeth with ALBO-CA, 10 (55.56 %) teeth with ALBO-CS, and 11 (60.95 %) teeth with MTA cement. A statistically significant difference in the results of pulp inflammatory response was found only when comparing the presence of a small number of polymorphonuclear leukocytes between ALBO-CS and MTA cement (Kruskal Wallis H test p=7.8255). A fully formed dentine bridge was recorded only after the application of ALBO-CA with a statistically significant difference compared to ALBO-CS and MTA (F test p=0.519, S-test p=0.656, Man-Whitney test p=2.802, Chi-square test p=4.747). Thirty days after the direct pulp capping with ALBO-CA, ALBO-CS, and MTA cements, bacteria were absent in rat teeth and surrounding tissue. Newly synthesized calcium aluminate ALBOCA showed good reparative abilities and possible use in direct pulp capping therapy.